Investigation on the Potential Correlation Between TP53 and Esophageal Cancer - Yao, Lihua; Zhong, Xiaowu; Huang, Guangcheng; Ma, Qiang; Xu, Lei; Xiao, Hong; Guo, Xiaolan (Frontiers in Cell and Developmental Biology, 2021)
Background TP53 family members play an indispensable role in a variety of human cancers, while the gene expression profiles, prognostic value, and potential mechanism in esophageal cancer (ESCA) are yet unclear. Methods The expression and roles of TP53 family members in ESCA were investigated using the Cancer Genome Atlas (TCGA), Tumor Immune Estimation Resource (TIMER), Kaplan–Meier plotter, Gene set enrichment analysis (GSEA), and UALCAN databases. The expression of TP53 between ESCA with the corresponding adjacent tissues was validated using qRT-PCR. Furthermore, the effects of TP53 on ESCC cell migration and proliferation were examined using the Transwell assay, scratch test, and crystal violet assay. The correlation between the TP53 and mTOR pathways was evaluated by Western Blotting. Results This study showed a noticeable correlation between high mRNA expression of TP53 members (TP53, TP63, and TP73) with clinical cancer stages and nodal metastasis status in ESCA patients. Moreover, the expression of TP53 was significantly associated with overall survival (OS) of ESCA patients. Additional experiments verified that the mRNA of TP53 was upregulated in esophageal squamous cell carcinoma (ESCC) patients. Moreover, the downregulated expression of TP53 significantly retarded ESCC cell migration and proliferation and may be participated in AKT-mTOR signaling pathway and TP53-dependent autophagy. Conclusion TP53 has a prognostic value in ESCA and may be a leading factor in promoting ESCA pathogenesis.